Paleomicrobiology to investigate copper resistance in bacteria: isolation and description of Cupriavidus necator B9 in the soil of a medieval foundry - David C. Gillan; Camille Van Camp; Max Mergeay; Ann Provoost; Nicolas Thomas; Laurent Vermard; Gabriel Billon; Ruddy Wattiez (Environmental Microbiology, 2017)
Summary Remains of a medieval foundry were excavated by archaeologists in 2013 in Verdun (France). Ancient workshops specialized in brass and copper alloys were found with an activity between 13th to 16th c. Levels of Cu, Zn and Pb reached 20000, 7000 and 6000 mg kg −1 (dw), respectively, in several soil horizons. The objective of the present work was to examine the microbial community in this contaminated site. A total of 8–22 10 6 reads were obtained by shotgun metagenomics in four soil horizons. Bioinformatic analyses suggest the presence of complex bacterial communities dominated by Proteobacteria. The structure of the community was not affected by metals, contrary to the set of metal‐resistance genes. Using selective media, a novel strain of Cupriavidus necator (eutrophus) , strain B9, was isolated. Its genome was sequenced and a novel metal resistance gene cluster with Hg resistance genes ( merRTPCA ) followed by 24 copper‐resistance genes ( actP, cusCBAF , silP , copK1 , copH4QLOFGJH3IDCBARS , copH2H1, copK2 ) was found. This cluster is partly homologous to the cop genes of Cupriavidus gilardii CR3 and C. metallidurans CH34. Proteomics indicated that the four copH genes were differentially expressed: CopH1 and CopH2 were mostly induced by Cd while CopH4 was highly expressed by Cu.

Heavy metal resistance in Cupriavidus metallidurans CH34 is governed by an intricate transcriptional network - Pieter Monsieurs; Hugo Moors; Rob Van Houdt; Paul J. Janssen; Ann Janssen; Ilse Coninx; Max Mergeay; Natalie Leys (BioMetals, 2011)

Diversity of endophytic bacteria from the cuprophytes Haumaniastrum katangense and Crepidorhopalon tenuis - Alfred Cubaka Kabagale; Bertrand Cornu; Françoise van Vliet; Claire-Lise Meyer; Max Mergeay; Jean-Baptiste Lumbu Simbi; Louis Droogmans; Corinne Vander Wauven; Nathalie Verbruggen (Plant and Soil, 2010)

The response of Cupriavidus metallidurans CH34 to spaceflight in the international space station - Natalie Leys; Sarah Baatout; Caroline Rosier; Annik Dams; Catherine s’Heeren; Ruddy Wattiez; Max Mergeay (Antonie van Leeuwenhoek, 2009)

Introduction to a special Festschrift issue celebrating the microbiology of Cupriavidus metallidurans strain CH34 - Simon Silver; Max Mergeay (Antonie van Leeuwenhoek, 2009)

New mobile genetic elements in Cupriavidus metallidurans CH34, their possible roles and occurrence in other bacteria - Rob Van Houdt; Sébastien Monchy; Natalie Leys; Max Mergeay (Antonie van Leeuwenhoek, 2009)

Plasmids captured in C. metallidurans CH34: defining the PromA family of broad-host-range plasmids - Géraldine A. Van der Auwera; Jaroslaw E. Król; Haruo Suzuki; Brian Foster; Rob Van Houdt; Celeste J. Brown; Max Mergeay; Eva M. Top (Antonie van Leeuwenhoek, 2009)

ArsR arsenic-resistance regulatory protein from Cupriavidus metallidurans CH34 - Yian-Biao Zhang; Sébastien Monchy; Bill Greenberg; Max Mergeay; Oleg Gang; Safiyh Taghavi; Daniel van der Lelie (Antonie van Leeuwenhoek, 2009)

Lead(II) resistance in Cupriavidus metallidurans CH34: interplay between plasmid and chromosomally-located functions - Safiyh Taghavi; Celine Lesaulnier; Sebastien Monchy; Ruddy Wattiez; Max Mergeay; Daniel van der Lelie (Antonie van Leeuwenhoek, 2009)

Use of the rotating wall vessel technology to study the effect of shear stress on growth behaviour of Pseudomonas aeruginosa PA01 - Aurélie Crabbé; Patrick De Boever; Rob Van Houdt; Hugo Moors; Max Mergeay; Pierre Cornelis (Environmental Microbiology, 2008)
Summary The biofilm phenotype of Pseudomonas aeruginosa enables this opportunistic pathogen to develop resistance to the immune system and antimicrobial agents. Pseudomonas aeruginosa biofilms are generated under varying levels of shear stress, depending on the infection site. In the lung mucus of cystic fibrosis (CF) patients, P. aeruginosa forms matrix‐enclosed microcolonies which cause chronic infections representing the major cause of mortality in CF patients. The lung mucus of CF patients is probably characterized by low fluid shear as the main shear‐causing factor, i.e. mucociliary clearance, is absent. In this study, the influence of fluid shear on the growth behaviour of P. aeruginosa PA01 was investigated using a low‐shear suspension culture device, the rotating wall vessel (RWV). Cultivation in low shear induced a self‐aggregating phenotype of P. aeruginosa PA01, resulting in the formation of biofilms in suspension similar to what has been described in CF mucus. The addition of a ceramic bead to the culture medium in the RWV created a higher‐shear condition which led to the formation of surface‐attached rather than suspension biofilms. In low‐shear culture conditions, a significant increase of the rhl N ‐butanoyl‐ l ‐homoserine lactone (C 4 ‐HSL) directed quorum sensing (QS) system, and the psl polysaccharide synthetic locus was demonstrated using gene expression analysis. Accordingly, the low‐shear condition induced a higher production of rhamnolipids, which is controlled by the C 4 ‐HSL QS‐system and is known to play a role in CF lung pathology. These results indicate that fluid shear has an impact on the growth phenotype of P. aeruginosa which might play a role in CF lung infections caused by this bacterium.

Diversity of Frankia strains associated to Myrica gale in Western Europe: impact of host plant ( Myrica vs. Alnus ) and of edaphic factors - Valérie Huguet; Max Mergeay; Emilio Cervantes; Maria P. Fernandez (Environmental Microbiology, 2004)
Summary Myricaceae can be nodulated by a variety of Frankia strains isolated from other actinorhizal families. Consequently, the genus Myrica has been considered to have low specificity with respect to microsymbiont taxa. In contrast to controlled studies of Myrica infectious capacity, field studies in North America have indicated that M. gale symbionts belong to the genetic group of Alnus ‐infective strains. Myrica gale is the most widely distributed species in the genus so this study focused on describing the genetic diversity of M. gale ‐nodulating strains from 10 sites in Western Europe across a range of edaphic conditions. When possible, the specificity of M. gale ‐infective strains was compared with that of Alnus ‐infective strains from the same sites. Nodular strains from Belgium, France and Spain were characterized using PCR‐RFLP of rrs gene and 16S‐23S IGS. rrs ‐RFLP patterns showed a high level of homogeneity among European strains with one dominant genotype. IGS‐RFLP patterns revealed the largest inter and intrasite diversity in France. In Belgium, Frankia strains were found to occur in two groups according to soil pH and organic matter characteristics of the sites. European M. gale ‐infective strains were genetically different from European Alnus and North American M. gale ‐infective strains indicating the possibility of different pathways of co‐evolution among geographically isolated populations.

Community shifts in a seeded 3‐chlorobenzoate degrading membrane biofilm reactor: indications for involvement of in situ horizontal transfer of the clc ‐element from inoculum to contaminant bacteria - Dirk Springael; Kurt Peys; Annemie Ryngaert; Sandra Van Roy; Liliane Hooyberghs; Roald Ravatn; Marc Heyndrickx; Jan‐Roelof van der Meer; Carlo Vandecasteele; Max Mergeay; Ludo Diels (Environmental Microbiology, 2002)
Summary Pseudomonas putida BN210, carrying the self‐ transferable clc ‐element encoding degradation of 3‐chlorobenzoate on the chromosome, was used as inoculum in different membrane biofilm reactors treating 3‐chlorobenzoate‐contaminated model wastewater. Analysis of the bacterial population in the effluent and in the biofilm showed the loss of BN210 beyond detection from the reactors and the appearance of several novel 3‐chlorobenzoate mineralizing bacteria mainly belonging to the β ‐proteobacteria. In contrast, in non‐inoculated reactors, no 3‐chlorobenzoate degradation was observed and no 3‐chlorobenzoate degraders could be recovered. Southern blots hybridization of genomic DNA using clc ‐element‐specific probes and FIGE analysis indicated the presence of the complete clc ‐element in one or more copies in the isolates. Moreover, the isolates could transfer the clc genes to Ralstonia metallidu‐rans recipients. Two representative reactor isolates, Ralstonia sp. strains KP3 and KP9 demonstrated a higher growth rate on 3‐chlorobenzoate than strain BN210 in batch cultures. When BN210, KP3 and KP9 were simultaneously inoculated in a membrane reactor supplied with 3‐chlorobenzoate, strain KP3 outcompeted the two other strains and remained the major 3‐chlorobenzoate degrading population in the reactor. Our data suggest that in situ horizontal transfer of the clc ‐element from the inoculum to contaminant bacteria in the reactors was involved in the establishment of novel 3‐chlorobenzoate degrading populations that were more competitive under the defined reactor conditions than the inoculum strain.

Transfer and expression of PCB-degradative genes into heavy metal resistantAlcaligenes eutrophus strains - Dirk Springael; Ludo Diels; Max Mergeay (Biodegradation, 1994)

RP4::miniMu (pULB113), a genetic tool to study bacterial genomes: application toPseudomonas fluorescens 6.2 - Max Mergeay; Philippe Lejeune; Jozef Gerits; Luc Fabry (Antonie van Leeuwenhoek, 1984)